Sensorless control of permanent magnet synchronous motor - Urbanski, Konrad; Zawirski, Krzysztof (Видавництво Національного університету «Львівська політехніка», 2003)
In the paper a problem of speed and position estimation in sensorless control of PMSM drive is discussed. A presented concept is a modification of solution based on detecting back EMF, induced in stator windings. A new structure of adaptive observer with proportional-integral function of corrector was introduced. Both simulation and experimental results show good properties of proposed observer structure.